Work Motivation of Health Workers in Providing Health Services during the COVID-19 Pandemic at the Anutoluwu Public Health Center, Petasiabarat District, North Morowali Regency - Mutmainnah HS; Joddy Permata Putra Lataa; Anggri Yunita Assa; Janice Sepang; Juliana Neng Rifka; Sabarulin Sabarulin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The addition and spread of Covid-19 cases globally is taking place quite quickly. The spread of Covid-19 also has an impact on various sectors, ranging from the economy, tourism, transportation, politics to public services, including health services at puskesmas. Data on patient visits at the Anutoluwu Health Center shows that there has been a decrease in patient visits since 2018. The purpose of this study is to find out the work motivation of health workers in providing health services during the Covid-19 pandemic at Anutoluwu Health Center, Petasia Barat District, North Morowali Regency. This type of research is descriptive research. The research variable is the work motivation of health workers in providing health services during the Covid-19 pandemic. The types of data are primary and secondary data. Data analysis is univariate analysis. The population in this study were all health workers at the Anutoluwu Health Center as many as 47 people. The sample is 47 people. The technique of determining the sample is the total population. The results showed that there were more respondents who had high work motivation in providing health services during the Covid-19 pandemic, which was 70.2% compared to those who had low work motivation, which was 29.8%. The conclusion of this study is that there are more health workers at the Anutoluwu Health Center, Petasia Barat District, North Morowali Regency who have high motivation in providing health services during the Covid-19 pandemic. It is recommended for Anutoluwu Health Center officers to stay enthusiastic and continue to increase their work motivation in providing health services during the Covid-19 pandemic, so that the image of the Puskesmas will remain good in the eyes of the community.